2015
DOI: 10.4103/0019-509x.178408
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S transferase (GSTP 1, GSTM 1, and GSTT 1) gene polymorphisms in Egyptian patients with acute myeloid leukemia

Abstract: We demonstrated that GSTM1 null or GSTT1 null genotypes may be considered independent risk factors for AML with no impact on prognosis and GSTP1 * 105 genotype is a prognostic factor, adding independent information to the routine laboratory parameters and cytogenetic and molecular alterations of the tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…In this case-control study, we found that the GSTM1 and GSTT1 deletion polymorphisms were associated with risk of AML these findings are partially agree with study done in Egypt [13] which demonstrated that GSTM1 null or GSTT1 null genotypes may be considered independent risk factors for AML. This study indicated GSTs polymorphisms were promising candidate biomarkers for evaluating the AML risk.…”
Section: Discussionsupporting
confidence: 90%
“…In this case-control study, we found that the GSTM1 and GSTT1 deletion polymorphisms were associated with risk of AML these findings are partially agree with study done in Egypt [13] which demonstrated that GSTM1 null or GSTT1 null genotypes may be considered independent risk factors for AML. This study indicated GSTs polymorphisms were promising candidate biomarkers for evaluating the AML risk.…”
Section: Discussionsupporting
confidence: 90%
“…Many conditions have been associated with the deletion polymorphisms in GSTM and G STT genes, including asthma ( Lima et al , 2010 ), male infertility ( Dordevic et al , 2010 ), end-stage renal disease ( Suvakov et al , 2013 ), leukemia ( Souza et al , 2008 ; Nasr et al , 2015 ) and lung cancer ( Sharma et al , 2015 ; Yang et al , 2015 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the GSTM family of genes have critical roles in several cancer types. GSTM1 is highly polymorphic in humans and is associated with multiple cancer types, such as bladder and breast cancer, metabolic disorders and autoimmune diseases, as well as anticancer drugs response and resistance ( 28 ) GSTM1 deletion in humans was indicated to have a key role in bladder ( 29 ) and breast cancer ( 30 , 31 ), multiple sclerosis ( 32 ), severe early-onset mental disorders including schizophrenia-spectrum disorder, bipolar disorder with psychotic symptoms or first-episode psychosis ( 33 ) and acute myeloid leukemia ( 34 ). Csejtei et al ( 35 ) identified that GSTM1 may be a prognostic biomarker in clinical diagnostics as well as a potential therapeutic candidate in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%